The impact of patient age on breast cancer risk prediction models. Issue 4 (8th January 2018) - Coopey, Suzanne B.; Acar, Ahmet; Griffin, Molly; Cintolo‐Gonzalez, Jessica; Semine, Alan; Hughes, Kevin S.
Abstract: Background: The impact of age on breast cancer risk model calculations at the population level has not been well documented. Methods: Retrospective analysis of formal breast cancer risk assessment in 36 542 females ages 40‐84 at a single institution from 02/2007 to 12/2009. Five‐year and lifetime breast cancer risks were calculated using Gail, Tyrer‐Cuzick version 6 (TC6), Tyrer‐Cuzick version 7 (TC7), BRCAPRO, and Claus models. Risk of BRCA mutation was calculated using BRCAPRO, TC6, TC7, and Myriad. Eligibility for BRCA testing was assessed using NCCN guidelines. Descriptive analyses were performed and trends in risk were assessed by age. Results: The lifetime risk of breast cancer trended down with increasing age in all risk models. TC7 calculated the highest estimates for lifetime risk for all age ranges and had the highest proportion of patients with a calculated lifetime risk >20%. Five‐year risk increased with age in all models. By age 60‐64, every risk model predicted a mean 5‐year risk ≥1.7%. Myriad estimated >5% risk of BRCA mutation more often than other models for all ages. Risk of BRCA mutation stayed constant with age with Myriad, but trended down with increasing age with TC6, TC7, and BRCAPRO. Conclusions: More patients have an estimated lifetime risk of breast cancer >20% and qualify for MRI screening with the Tyrer‐Cuzick model. All models predict an increased 5‐year risk with age, which could impact chemoprevention recommendations. To maximize access to genetic testing, the Myriad model and NCCN guidelines should be used.